Übersichtstafel von dem Arbeitsgebiet der Deutschen Antarktischen Expedition 1938-39 Neuschwabenland - Richter, Hans; Förstner, Rudolf (Reproduction (1986) by: Institut für Angewandte Geodäsie (Now: Bundesamt für Kartographie und Geodäsie) Frankfurt am Main, 1986)
Reproduction of south-facing Topographic survey map "Neu-Schwabenland 1:1 500 000" of the area of operation of the German Antarctic Expedition 1938/39 (DAE 1938/39), Reproduction downscaled to 1:2 000 000 scale, Annex 1 of 17, Brunk, K. (1986); Scale: 1:2000000 Projection: Transverse conformal cylindric Bounding Box: POLYGON ((-10 -68.5, 20 -68.5, 23 -75, -18 -75, -10 -68.5))